Improvisation Pedagogy: An Epistemological Perspective of the 4‘E’ Model within Digital Musical Instruments - Corintha, Isabela; Cabral, Giordano (Revista Vórtex, 2022)
Recent years have witnessed the appearance of many new digital musical instruments (DMIs) and other interfaces for musical expression (NIME). This paper highlights a well-established music educational background theory that we believe may help DMI developers and users better understand DMIs in the context of music cognition and education. From an epistemological perspective, we present the paradigm of enactive music cognition related to improvisation in the context of the skills and needs of 21st century music learners. We hope this can lead to a deeper insertion of DMIs into music education, as well as to new DMIs to be ideated, prototyped and developed within these concepts and theories in mind. We specifically address the theory generally known as the 4E model of cognition (embodied, embedded, extended and enactive) within DMIs. The concept of autopoiesis is also described. Finally, we present some concrete cases of DMIs and NIMEs, and we describe how the experience of musical improvisation with them may be seen through the prism of such theories.